2014
DOI: 10.1021/jp5014785
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Flexibility of Mephenesin

Abstract: The mephenesin molecule (3-(2-methylphenoxy)propane-1,2-diol) serves as a test bank to explore several structural and dynamical issues, such as conformational flexibility, the orientation of the carbon linear chain relative to the benzene plane, or the effect of substituent position on the rotational barrier of a methyl group. The molecule has been studied by rotational spectroscopy in the 4-18 GHz frequency range by Fourier-transform methods in a supersonic expansion. The experiment has been backed by a previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…For o-cresol (2), Welzel et al also reported on both the syn-and the anti-conformers [143]. Due to steric hindrance arising from the bulkier methoxy group, only the anti-conformer of o-methylanisole (9) [127] was observed; the syn-conformer was too high in energy, similar to the situation found for mephenesin (12) [152].…”
Section: Cresol and Methylanisole Derivativesmentioning
confidence: 65%
See 2 more Smart Citations
“…For o-cresol (2), Welzel et al also reported on both the syn-and the anti-conformers [143]. Due to steric hindrance arising from the bulkier methoxy group, only the anti-conformer of o-methylanisole (9) [127] was observed; the syn-conformer was too high in energy, similar to the situation found for mephenesin (12) [152].…”
Section: Cresol and Methylanisole Derivativesmentioning
confidence: 65%
“…Although some chemical properties such as vapor pressure, color, smell, and acidity are similar, the effects of methyl internal rotation, which often depend on the steric and electronic surroundings, are completely different for these isomers, as shown in Figure 5. 1) The prototype toluene [137][138][139][140][141][142], (2) o-cresol [143], (3) m-cresol [144], (4) p-cresol [145], (5) p-thiocresol [146], (6) anti-carvacrol (two conformers, A and B) [147], (7) syn-thymol [147], (8) creosol [148], (9) o-methyl anisole [127], (10) m-methyl anisole [149,150], (11) p-methylanisole [151], ( 12) mephenesin (two conformers, A and B) [152], (13) 3-methylphenylacetylene [153].…”
Section: Cresol and Methylanisole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Commonly used protocols such as Catalyst [24], MOE [25] and MacroModel [26] implement both approaches [15, 27]. Significance of the conformational sampling and challenges in finding the bioactive pose among an ensemble of generated conformers were previously discussed in several studies [14, 2832]. …”
Section: Introductionmentioning
confidence: 99%